Efficient Silicon Solar Cells for Space and Ground-Based Aircraft. (2015) - Latukhina, Natalya; Rogozin, Anton; Puzyrnaya, Galina; Lizunkova, Darya; Gurtov, Aleksandr; Ivkov, Sergey
Abstract: On the MCA "AIST 2" is planned the conduction of the experiment on the study of the outer space effects on the characteristics of experimental silicon photovoltaic cells (PVC)manufactured according to the technology developed in the Samara state University. Effective photovoltaic cells as sources of energy for aircraft are of great interest from developers of space technology, as for most of spacecraft solar panels are virtually non-alternative source of energy. Most high performance to date have nanoheterostructure PVC-based materials АIII BV . However, despite the fact that silicon solar cells inferior to them on such an important parameter as efficiency, silicon continues to be the main material of the photo power engineering. This is due to the prevalence of raw materials and advanced technology of manufacture of the material and devices on its basis, providing a significantly lower cost silicon solar cells in comparison with analogues on the basis of materials АIII BV . Therefore, the actual problem silicon solar cells is to increase their efficiency. Experimentally proved that silicon solar cells are not inferior in efficiency of energy conversion nanoheterostructures can be created on the basis of multilayer structures on single crystal silicon substrate in which there are materials with different band gap making it possible to reduce the fundamental losses in the crystal associated with nepogashenie photons with energy smaller than U (the width of the forbidden zone) of the crystal, and the thermalization of the crystal lattice in the absorption of photons with energy greater than Ed. Due to this, you can greatly exceed the theoretical limit of photovoltaic energy conversion to mono-silicon 27%[1] .